Unveiling the Origins and Dynamics of the Hierarchical Triple Star System CN Lyn - Yücel, Gökhan; Bakış, Volkan; Canbay, Remziye; Alan, Neslihan; Banks, Timothy; Bilir, Selçuk (American Astronomical Society, 2025)
In this study, we present a detailed analysis of CN Lyn, an overlooked triple star system, by combining spectroscopic data from the literature, photometric Transiting Exoplanet Survey Satellite data, and kinematic techniques. We updated the fundamental parameters of the known eclipsing components in the system with high precision. The chemical composition of both eclipsing components (Aab) and the third component (B) in the system were calculated with great accuracy. According to our analysis the mass, radius, and metallicity of the eclipsing components are 1.166-0.012+0.013M circle dot , 1.786-0.014+0.013R circle dot , and -0.78-0.02+0.02 dex for Aa and 1.143-0.012+0.013M circle dot , 1.651-0.013+0.014R circle dot , and -0.55-0.02+0.03 dex for Ab. The pair's age is 3.89-0.10+0.10 Gyr. The mass, radius, metallicity, and age for B are 0.85-0.23+0.23M circle dot , 1.436-0.023+0.026R circle dot , -1.83-0.11+0.09 dex, and 12.5-2.5+2.5 Gyr, respectively. It is also found that the triple system (AabB) satisfies the stability criteria for the hierarchical triple system. Kinematic and Galactic orbital parameters of CN Lyn were obtained from the astrometric and spectroscopic data of the system. Dynamical orbital analyses, taking into account the ages of the component stars in the central binary system (A), show that the CN Lyn originated at the metal-poor edge of the Galactic disk. The third component of the system was found to be a member of the halo population in terms of age, alpha elements, and metal abundance. Given the different chemical abundances and age of B compared to A, this suggests that the third component was captured by the central system in a region with weak gravitational interactions far beyond the Galactic disk.